2017
DOI: 10.1371/journal.pone.0188513
|View full text |Cite
|
Sign up to set email alerts
|

Implicit theories concerning the intelligence of individuals with Down syndrome

Abstract: Studies over the past three decades have shown that learning difficulties are not only determined by neurological disorders, but also by motivational and/or socio-cognitive factors Among these factors, implicit theories of intelligence (also referred to as conceptions, mindsets or beliefs about intelligence) are key elements. The belief that intelligence is fixed (entity theory), as opposed to malleable (incremental theory), is generally associated with negative teaching practices and poorer student outcomes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
2
5
0
1
Order By: Relevance
“…H1 was supported, with participants showing more entity views of intelligence towards those with ID and greater incremental views of intelligence towards those without ID. This lends support to the limited previous research, which likewise found participants to hold more entity views of intelligence in people with IDspecifically Down's syndrome (Enea-Drapeau et al, 2017).…”
Section: Attitudes Towards Intelligence and Intellectual Disabilitysupporting
confidence: 84%
See 1 more Smart Citation
“…H1 was supported, with participants showing more entity views of intelligence towards those with ID and greater incremental views of intelligence towards those without ID. This lends support to the limited previous research, which likewise found participants to hold more entity views of intelligence in people with IDspecifically Down's syndrome (Enea-Drapeau et al, 2017).…”
Section: Attitudes Towards Intelligence and Intellectual Disabilitysupporting
confidence: 84%
“…To date, very few studies have used TOI to examine attitudes towards offenders, with none examining attitudes towards offenders with ID. Enea-Drapeau et al (2017) investigated the impact of TOI on explicit judgements and implicit attitudes towards clients with Downs syndrome. They found that both professionals and the general population had higher entity views of intelligence for people with ID and greater entity views correlated with more negative explicit judgements.…”
Section: Theories Of Intelligencementioning
confidence: 99%
“…Indeed, in general teachers report they do perceive student intelligence as malleable more than they report believing it to be fixed. However certain exceptions exist: teachers working with disabled persons (Enea-Drapeau, Carlier, & Huguet, 2017) for example. Furthermore, mathematics teachers are more likely to report that they believe intelligence is fixed than teachers in the domains of languages, sciences and practical disciplines (Jonsson, Beach, Korp, & Erlandson, 2012.…”
Section: Selective Representationsmentioning
confidence: 99%
“…Respecto a nuestra primera pregunta ¿Cuáles son las teorías subjetivas que tienen los profesores que enseñan por primera vez a estudiantes con síndrome de Down? se puede concluir que se evidencia consenso en cuatro temáticas y disenso en dos, hay diversos factores que pueden aportar en la comprensión de estas diferencias en sus TS, uno de los que ha destacado la literatura es la experiencia profesional previa del docente (MacFarlane y Woolfson, 2013), por ejemplo se ha evidenciado cómo la experiencia profesional con niños con SD modifica las concepciones de inteligencia (Enea-Drapeau et al, 2017). El análisis permitió visualizar que las TS de ambas docentes evolucionaron de manera similar al concordar en el cambio de cuatro ejes: percepción del SD, apoyo laboral, estrategias pedagógicas y dificultades percibidas; mientras que se aprecia disenso en las creencias sobre la inclusión escolar y la visión del estudiante con SD.…”
Section: Discussionunclassified